Legal Protection by the Notary Honorary Council for Notaries in the Execution of Notarial Duties - Gentur Cahyo Setiono; Made Warka; Endang Prasetyawati; Rosalinda Elsina L (Technium Social Sciences Journal, 2025)
In a state governed by the rule of law, every action taken by state officials as well as members of society must be grounded in law to achieve legal certainty, justice, and utility. The notary, as a public official regulated under the Notary Office Act (UUJN), holds an essential role in realizing these principles. Article 15 of the UUJN explicitly grants authority to notaries to draw up authentic deeds concerning all acts, agreements, and determinations desired by the parties or required by law. With this authority, notaries do not merely function as “deed-makers,” but also as guarantors of legal certainty because the authentic deeds they produce possess perfect evidentiary value in civil procedural law. This study employs normative juridical research by analyzing legislation governing the authority of the Notary Honorary Council in the execution of notarial duties. The approaches used include the statutory approach and the conceptual approach. This study aims to identify the meaning and qualifications of “good and correct law” that should underlie legal protection for the notarial profession. The Notary Honorary Council holds an important authority in providing legal protection to notaries in performing their duties. However, this protection is not yet optimal because the MKN does not hold the authority to impose administrative sanctions; such authority lies with the MPN. Therefore, the MKN must be granted authority to submit its examination results to the MPN as recommendations for administrative sanctions, ensuring institutional coordination between the MKN and MPN. Such regulation would actualize legal protection and legal certainty for notaries, consistent with Gustav Radbruch’s theory of legal certainty and Philipus M. Hadjon’s theory of legal protection, enabling notaries to perform their officium nobile with safety, independence, and professionalism.